KNOWLEDGE WITH COMMUNITY STIGMA ABOUT LUNG TB DISEASE DURING THE COVID-19 PANDEMIC IN SUMURGUNG VILLAGE, TUBAN DISTRICT - Putri, Sabillah Darma; sumiatin, titik (Global Ten Public Health and Nursing Journal, 2023)
Many people today underestimate pulmonary TB because it is considered an old disease. During the current Covid-19 pandemic, people affected by Covid-19 have the same symptoms as pulmonary TB, thus making people confused and causing an increase in pulmonary TB cases. This can also be influenced by the lack of public knowledge about pulmonary TB disease during the Covid-19 Pandemic. Based on the initial survey conducted on 27 June 2022 in Sumurgung Village, 7 out of 10 people have the wrong stigma about pulmonary TB. The purpose of this study was to determine the relationship between knowledge and public stigma about pulmonary TB disease during the Covid-19 pandemic. The research design used correlation analytic with cross sectional approach. The population in this study were all households in RW 06 Dusun Mbongkol 2 Sumurgung Village, with a sample size of 148 households. The sampling technique is purposive sampling, the variables in this study are public knowledge and public stigma about pulmonary TB in the Covid-19 Pandemic Period. Data collection tools in the form of questionnaires were then tabulated and analyzed by chi-square test. The results of this study indicate that almost half of the people with good knowledge have a positive stigma of 45 people (73%) and almost all of the people who have less knowledge have a negative stigma of 42 people (95%). The test results show p value = 0.000 then there is a relationship between knowledge and stigma. People who have less knowledge cause negative stigma, so that it can be a factor that causes TB cases to increase. Efforts to increase public knowledge are by providing health education to the community, so as to reduce the negative stigma of the community about pulmonary TB in the Covid-19 Pandemic Period